A qualitative study exploring clinicians’ views on clinical trials in thumb carpometacarpal joint osteoarthritis - Benjamin J. F. Dean; Cynthia Srikesavan; Robin Horton; Francine Toye (Bone & Joint Open, 2022)
Aims Osteoarthritis (OA) affecting the thumb carpometacarpal joint (CMCJ) is a common painful condition. In this study, we aimed to explore clinicians’ approach to management with a particular focus on the role of specific interventions that will inform the design of future clinical trials. Methods We interviewed a purposive sample of 24 clinicians, consisting of 12 surgeons and 12 therapists (four occupational therapists and eight physiotherapists) who managed patients with CMCJ OA. This is a qualitative study using semi-structured, online interviews. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results A total of 14 themes were developed, six of which were developed relating to the clinical management of CMCJ OA: 1) A flexible ‘ladder’ approach starting with conservative treatment first; 2) The malleable role of steroid injection; 3) Surgery as an invasive and risky last resort; 4) A shared and collaborative approach; 5) Treating the whole person; and 6) Severity of life impact influences treatment. The remaining eight themes were developed relating to clinical trial barriers and facilitators: 1) We need to embrace uncertainty; 2) You are not losing out by taking part; 3) It is difficult to be neutral about certain treatments; 4) Difficult to recruit to ‘no treatment’ ; 5) Difficult to recruit to a trial comparing no surgery to surgery; 6) Patients are keen to participate in research; 7) Burden on staff and participants; and 8) A enthusiasm for a variety of potential trial arms. Conclusion Our findings contribute to a better understanding of how clinicians manage thumb CMCJ OA in their practice settings. Our study also provides useful insights informing the design of randomized clinical trials involving steroid injections and surgery in people with thumb CMCJ OA. Cite this article: Bone Jt Open 2022;3(4):321–331.